95 Carbohydrase Mixture Supplementation to High Fiber Diets on Apparent Total Tract Digestibility of Nutrients in Diets for Gestating Sows Compared with Growing Pigs. (12th April 2022) - Shipman, Garrin; Perez-Palencia, Jorge Y; Patterson, Rob; Levesque, Crystal L
Abstract: The objective of this study was to compare the apparent total tract digestibility (ATTD) of nutrients and non-starch polysaccharides (NSP) between gestating sows and growing pigs fed a high fiber (NDF = 17.5%) diet with or without supplemental carbohydrase mixture (CM). Forty-five gestating sows (parity 0 to 5; BW 187 ± 28 kg) and 27 growing pigs (initial BW 35.7 ± 3.32 kg) were allotted to 3 levels of CM inclusion ('0' '0.08' and '0.10'%). Sows were fed once daily at 2.2 kg/d and grower pigs provided feed at 5% of BW to reflect ad libitum feed access. Titanium (0.3%) was the indigestible marker, and feces were collected for 4 d following a 10-d adaption period. Data were analyzed in a 2 × 3 factorial arrangement with main effects of animal category (gestating sow or grower pig) and CM supplementation. Dietary CM supplementation increased ( P < 0.05) ATTD of all nutrients except for NDF with tendency ( P < 0.10) for increase in arabinose and glucose digestibility. There were no differences between the 0.08% and 0.1% CM inclusion levels (Table 1). Regardless of enzyme supplementation, ATTD of calcium and phosphorus were higher in the grower pigs ( P < 0.01). Sows displayed increased ( P < 0.05) ATTD of NDF, xylose, glucose, total NSP with tendency ( P < 0.10) for ADF and arabinose in comparison to grower pigs. An interaction was detected ( P = 0.036) where ATTD of phosphorus increased with 0.08 and 0.10% CM inclusion in grower pigs and only with 0.10% in sows. Dietary CM supplementation can increase ATTD of nutrients, NSP, and energy in high fibrous diets. Lastly, sows have higher digestibility of dietary fiber in comparison to grower pigs irrespective of enzyme supplementation.